PEMBERDAYAAN KELOMPOK SADAR WISATA (POKDARWIS) DALAM PENGELOLAAN EKOWISATA BERBASIS KOMUNITAS DI PULAU KOSIOK - Iskandar, Iskandar; Putra, Eka; Hendra, Teguh; Anuar, Saiful; Aziz, Abdul; Mardan, J Ardan (Penerbit Widina, Widina Media Utama, 2025)
This community service activity was carried out with the aim of providing intensive assistance to members of the Tourism Awareness Group (POKDARWIS) in Muara Jalai Village, North Kampar District, Kampar Regency, related to ecotourism management. This assistance included socialization, training, and evaluation of local resource potential. The methodology applied in this activity was direct socialization to the community. The main target of this community service activity was POKDARWIS members who were actively involved in the management of the tourist village. Group members were provided with training, socialization, assistance, and empowerment programs in order to optimize ecotourism management. The results of the community service show high motivation among members of the tourism awareness group in designing ecotourism management strategies, developing facilities according to needs, maintaining tourism assets, and promoting and empowering the economy of the community around tourist attractions.ABSTRAKKegiatan pengabdian kepada masyarakat ini dilaksanakan dengan tujuan memberikan pendampingan intensif kepada anggota Kelompok Sadar Wisata (POKDARWIS) di Desa Muara Jalai, Kecamatan Kampar Utara, Kabupaten Kampar, terkait tata kelola ekowisata. Pendampingan ini mencakup kegiatan sosialisasi, pelatihan, serta evaluasi potensi sumber daya lokal. Metodologi yang diterapkan dalam kegiatan ini adalah sosialisasi langsung kepada masyarakat. Sasaran utama kegiatan pengabdian ini adalah anggota POKDARWIS yang secara aktif terlibat dalam pengelolaan desa wisata. Anggota kelompok diberikan pembekalan berupa pelatihan, sosialisasi, pendampingan, serta program pemberdayaan dalam rangka optimalisasi pengelolaan ekowisata. Hasil pengabdian menunjukkan adanya motivasi yang tinggi dari anggota kelompok sadar wisata dalam merancang strategi pengelolaan ekowisata, pengembangan fasilitas sesuai kebutuhan, pemeliharaan aset wisata, serta promosi dan pemberdayaan ekonomi masyarakat di sekitar objek wisata.